2015
DOI: 10.1186/s12944-015-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genetic variants at newly identified lipid gene TRIB1 with coronary heart disease in Chinese Han population

Abstract: BackgroundRecent genome-wide association studies (GWAS) have identified the variants near TRIB1 gene affecting blood lipid levels. However, the association between the reported variants and risk of coronary heart disease (CHD) was not confirmed.MethodsWe conducted two independent case–control studies. The first study consisted of 300 CHD patients and 300 controls and the second study had 1,332 CHD patients and 2,811 controls. The genotypes of two variants rs3201475 and rs17321515 in TRIB1 were determined by Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…Tai et al investigated the effect of TRIB1 rs17321515 in Malay population, the results showed that TRIB1 rs17321515 was significant associated with the elevated level of total cholesterol (TC) and low density lipoprotein (LDL), and the risk of cardiovascular disease (CVD) [16]. The elevated serum TG level and risk of coronary heart disease in TRIB1 rs17321515 A allele carriers in Chinese Han population were also be observed [17]. Varbo et al conducted a study to test the effect of TRIB1 rs2954029 in the general population, the results showed that TRIB1 rs2954029 A allele carriers had the higher serum levels of TG, TC, apolipoprotein B, and LDL-C, and the lower high density lipoprotein (HDL) than A allele non-carriers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tai et al investigated the effect of TRIB1 rs17321515 in Malay population, the results showed that TRIB1 rs17321515 was significant associated with the elevated level of total cholesterol (TC) and low density lipoprotein (LDL), and the risk of cardiovascular disease (CVD) [16]. The elevated serum TG level and risk of coronary heart disease in TRIB1 rs17321515 A allele carriers in Chinese Han population were also be observed [17]. Varbo et al conducted a study to test the effect of TRIB1 rs2954029 in the general population, the results showed that TRIB1 rs2954029 A allele carriers had the higher serum levels of TG, TC, apolipoprotein B, and LDL-C, and the lower high density lipoprotein (HDL) than A allele non-carriers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had reported the effect of TRIB1 rs17321515 on the serum lipids metabolism. In a Chinese Han cohort study, TRIB1 rs17321515 AA genotype carriers had higher TG level than GG genotype carriers [42]. Katalin et al also found that TRIB1 rs17321515 AA genotype carriers had higher serum TG and TC levels than GG + GA genotypes carriers [43].…”
Section: Discussionmentioning
confidence: 99%
“…The encoded LAMC1 protein is thought to mediate the attachment, migration and organization of cells into tissue during embryonic development as a result of its interaction with other cellular matrix components. Similarly, the TRIB1 which harbors the rs6982502 is involved in the regulation of hepatic lipogenesis, and has also been associated with plasma TG levels, ischemic heart disease (IHD) and familial hypercholesterolemia (59)(60)(61)(62). Currently, there is no data in the literature pertaining to the role of either this SNP or the encoding LAMC1 gene in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, apart from a suggestive role for this gene in lipid metabolism, the fact that the rs17145738 lies at a locus shared by these two genes may point to a regional genomic link to the disease and dyslipidemia-related cardiovascular disease, such as CAD. Similarly, the TRIB1 which harbors the rs6982502 is involved in the regulation of hepatic lipogenesis, and has also been associated with plasma TG levels, ischemic heart disease (IHD) and familial hypercholesterolemia (59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%